Simple semiclassical model of pressure-broadened infrared/microwave linewidths in the temperature range 200–3000 K. Issue 1 (26th July 2022) - Buldyreva, Jeanna; Yurchenko, Sergei N; Tennyson, Jonathan
Abstract: There is a need for line-broadening parameters for molecules found in exoplanetary atmospheres for a variety of broadeners and a range of temperatures. The use of an easily handled semiclassical theoretical expression is suggested for the calculation of pressure-broadened linewidths for (vib)rotational transitions over a large temperature range (200–3000 K) starting from a minimal set of input parameters: kinetic molecular properties and the character of the leading term in the intermolecular interaction potential. Applications to NO and OH colliding with rare-gas atoms and non-polar molecules demonstrate good consistency with available measurements over the full temperature range indicated. The procedure therefore can be expected to provide realistic estimates for line broadening of 'exotic' molecules and molecular ions present in hot planetary atmospheres.